PENINGKATAN BISNIS UMKM BERBASIS PRODUK OLAHAN IKAN DI PERUMNAS POASIA KOTA KENDARI - Salwiyah, Salwiyah; Abdul Rajab Nadia, La Ode; Zubaydah, Wa Ode Sitti; Afu, La Ode Alirman; Abdullah, Abdullah (Program Studi Ilmu Kelautan, FMIPA Universitas Tanjungp, 2025)
Diversification of processed food products based on fishery raw materials for The Micro, small, and medium enterprises (MSMEs) at Perumnas Poasia, Kendari City is one of the efforts to diversify food products derived from fish on a business scale. The aim of this activity is to increase knowledge, skills and community welfare through making fisheries products diversification. The partners of this PKM activity are MSME businesses at Perumnas Poasia, Kendari City. The activity implementation method includes two stages, they are socialization and training in making products such as meatballs and nuggets. It is hoped that MSME business actors can process local fish resources into food products that are more varied and attractive for consumption, and can improve community welfare through the production of diversified processed fish. This activity is important to increase the added value of products and the quantity of MSME products.